2018
DOI: 10.3390/su10124548
|View full text |Cite
|
Sign up to set email alerts
|

Fair or Unfair: The Moderating Effect of Sustainable CSR Practices on Anticipatory Justice Following Service Failure Recovery

Abstract: This paper investigates the relative effect of anticipatory justice on organizational legitimacy and consumer trust that further leads to consumer citizenship behavior following service failure recovery in Taiwan. Further, the moderating role of sustainable corporate social responsibility (CSR) practices is explored. A causal relationship and survey design with a valid sample of 269 respondents was applied. Findings indicated that organizational legitimacy and consumer trust can be restored through anticipator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 120 publications
1
3
0
Order By: Relevance
“…In doing so, we linked the studies with the transactional theory of stress and coping and argued that consumers' perceptions of CSR of e-commerce can be viewed as an effective concept for reducing consumers' negative responses and highlighted the role of attributions of responsibility. From this perspective, our ndings provide further evidence supporting that CSR is a more effective buffer when it comes to the consumer's point of view (Joireman et al, 2015;Kim & Park, 2020;Lii et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…In doing so, we linked the studies with the transactional theory of stress and coping and argued that consumers' perceptions of CSR of e-commerce can be viewed as an effective concept for reducing consumers' negative responses and highlighted the role of attributions of responsibility. From this perspective, our ndings provide further evidence supporting that CSR is a more effective buffer when it comes to the consumer's point of view (Joireman et al, 2015;Kim & Park, 2020;Lii et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…Second, although prior research examines fairness and uncertainty management in response to small change‐related events (Goldman et al, 2016; Lii et al, 2018; Rodell & Colquitt, 2009), we investigated unfairness in response to one of the largest, uncertainty‐instigating events: newcomer organisational entry. Given the frequency with which employees change jobs throughout their careers (U.S. Bureau of Labor Statistics, 2015), the organisational entry context is a unique, reoccurring and viable avenue to examine injustice appraisals.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although scholars have examined how employees manage uncertainty in response to smaller change‐related events (Goldman et al, 2016; Lii et al, 2018; Rodell & Colquitt, 2009), our two‐study investigation is the first to consider fairness and uncertainty management within the context of organisational entry. Because fairness estimations are exceedingly common in times of uncertainty (Takeuchi et al, 2012), and provided the frequency with which employees are changing organisations (Saks & Gruman, 2018), organisational entry is an excellent context to study the complexities of appraising the fairness of the work context.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that people tended to have negative views on profit-driven organizations. Yet, organizations have to embrace the concepts of virtuousness and the common good because our society values them and consumers are conscious and demand organizations to act morally and meet societal values (Lii et al, 2018). For this reason, organizations and their employees start seeing the importance of harmonizing the goals of individuals, organizations and the economy to achieve the greatest good (Arjoon et al, 2018).…”
Section: Perceived Societal Value Attitude and Intentionmentioning
confidence: 99%